Application of SNP in Genetic Sex Identification and Effect of Estradiol on Gene Expression of Sex-Related Genes in Strongylocentrotus intermedius - Han, Ya-Lun; Sun, Zhi-Hui; Chang, Shuai; Wen, Bin; Song, Jian; Zuo, Ran-Tao; Chang, Ya-Qing (Frontiers in Endocrinology, 2021)
Sea urchin (Strongylocentrotus intermedius) is an economically important mariculture species in Asia, and its gonads is the solely edible part. The efficiency of genetic breeding in sea urchins is hampered due to the inability to distinguish the gender by appearance. In this study, we first identified a sex-associated SNP by combining type IIB endonuclease restriction-site associated DNA sequencing (2b-RAD-seq) and genome survey. Importantly, this SNP locates within spata4, a gene specifically expressed in male. Knocking down of spata4 by RNA interference (RNAi) in male individuals led to the downregulation of other conserved testis-differentiation related genes and germ cell marker genes. We also revealed that the sex ratio in this validated culture population of S. intermedius is not 1:1. Moreover, after a 58-day feeding experiment with estradiol, the expression levels of several conserved genes that are related to testis differentiation, ovary differentiation and estrogen metabolism were dynamically changed. Taken together, our results will contribute to improving the breeding efficiency, developing the sex-controlled breeding, as well as providing a solid base for understanding the sex determination mechanisms in sea urchins.